Regional Language Interference in Indonesian Phonology among Elementary School Students - Kristofel Bere Nahak; Maria Magdalena Namok Nahak; Febronia Lasi; Yanuarius Seran; Adeline Lelo Lein; Jose Da Conceicao Verdial (Jurnal Penelitian dan Pengembangan Pendidikan, 2026)
This research is motivated by the difficulty educators face in designing learning evaluations using Indonesian as the medium of instruction for students with diverse mother tongue backgrounds. The gap between the policy of using Indonesian in schools and the reality on the ground, where students better understand material through regional languages, forms the basis of the urgency of this study. This research aims to analyze the effect of language use on student learning outcomes, particularly in the aspect of contemporary Indonesian phonology. This study uses a quantitative approach with primary school students as research subjects, divided into two groups based on the language used in the tests. The data collection technique was conducted through online multiple-choice tests using Google Form. The research instruments were analyzed through item quality tests, including discrimination index, difficulty level, and reliability, as well as further analyzed using differential item functioning (DIF) analysis. The results of the study indicated that students tended to achieve better learning outcomes when using their regional language compared to Indonesian. These findings indicate that language plays an important role in supporting student understanding. This research emphasizes the importance of considering the use of the mother tongue in the learning process. The practical implication of this study is the need for more inclusive educational policies that accommodate the use of local languages to improve the quality of learning and the equity of student learning outcomes.